THE ROLE OF INNOVATIVE PROJECTS IN THE ACTIVITIES OF BUSINESS ENTITIES IN THE GREEN ECONOMY (Web of Technology: Multidimensional Research Journal, 2025)
The article analyzes the importance of the green economy in Uzbekistan and its impact on economic, environmental and social development. The main principles of the green economy, including energy efficiency, sustainable use of natural resources, combating climate change and approaches to solving environmental problems, are considered. The priorities of the transition to “the green economy”, the purpose of the strategy for the transition to “the green economy” in Uzbekistan, the objectives, stages of development and the content of priorities are described.